Start-ups by the unemployed: characteristics, survival and direct employment effects - Marco Caliendo; Alexander S. Kritikos (Institute for the Study of Labor (IZA), 2007)
Fostering and supporting start-up businesses by unemployed persons has become an increasingly important issue in many European countries. These new ventures are being supported by various governmental programs. Potential benefits include not only the end of unemployment for the new entrepreneur but also some further positive effects, e.g., direct job creation. However, it is often feared that the previously unemployed lack the basic qualifications to become entrepreneurs. Empirical evidence on skill-composition, direct job creation and other key variables is rather scarce, largely because of inadequate data availability. We base our analysis on a unique and very informative survey data containing a representative sample of over 3,100 start-ups founded by unemployed persons in Germany. Individuals were subsidized under two different schemes, and we are able to draw on extensive pre- and post-founding information concerning the characteristics of the business (start-up capital, industry, etc.) and of the business founders (education, motivation, preparation, etc.). We find that formerly unemployed founders are motivated by push and pull factors. Using a proportional hazard duration model with unobserved heterogeneity allows us to analyze the characteristics which drive success of the businesses. While survival rates 2.5 years after business founding are quite high (around 70%) for both programs and genders, the characteristics of the newly developed businesses are heterogeneous.
Keywords: J68; 330; Start-up subsidies; self-employment; unemployment; direct employment effects; survival; Selbstständige; Arbeitslosigkeit; Unternehmensgründung; Subvention; Arbeitsmarktpolitik; Wirkungsanalyse; Unternehmensentwicklung; Beschäftigungseffekt; Deutschland